SELL AND BUY MINDRING AS A SOLUTION TO HOUSEHOLD NEEDS (REVIEW OF MUAMALAT FIQH) - Moh. Rasyid; Andri Amin Tawakal; Ahmad Budi Lakuanine (Universitas Islam Negeri Mataram, 2020)
The social reality of society always suggests differences, especially differences in the ability of financial or economic. There are high-income earners who are often known as rich, and there are also those who have low income who are known as poor or underprivileged. As a response to this reality, this paper specifically tries to offer a solution in the form of a buying and selling transaction model that is easily accessible to the underprivileged, to fulfill household needs. With the descriptive analysis method, this paper found a solution in the form of a mindring through the process of verification of Muamalat Fiqh, to measure the ability of these solutions practiced by the community. The results of this study indicate that selling and buying with mindring models provide solutions for people who are less able to fulfill household needs. In addition to the elements of the existing convenience, mindring offers as a solution is also due to ability in Muamalat Fiqh, as long as the practice does not violate the terms defined by Islamic law.